Routine detection and management of neurocognitive impairment in HIV-positive patients in a UK centre. (March 2013) - Haddow, L J; Cpsychoil, A Accoroni; Cartledge, J D; Manji, H; Benn, P; Gilson, R J C
We estimated the burden of HIV-associated neurocognitive disorders (HAND) in a UK clinic. From a random sample, and referrals to specialist services over one year (neurology, clinical psychology, hospital admissions), we determined whether patients were diagnosed with HIV-associated dementia (HAD) and whether they reported symptoms suggesting neurocognitive impairment (NCI). In the first sample, 2/150 (prevalence 1.3%; 95% confidence interval [CI] 0.2–4.7%) had documented HAD. Eleven patients (7.3%; CI 3.7–12.7%) reported recent symptoms suggesting NCI; most of these individuals were diagnosed with a psychiatric or substance-use disorder. Among specialist referrals with symptoms suggesting NCI, 11 were diagnosed with HAD from a clinic population of 3129 individuals (annual incidence 0.4%; CI 0.2–0.6%). No patients with mildly symptomatic or asymptomatic HAND were identified in either sample, suggesting that such patients remain undetected in current clinical practice. Evidence-based screening for HAND in HIV clinics may be needed.